Culturally Responsive Teaching: Improving Middle School Numeracy in Linear Functions - Brigita Wanda Pangestika; Nurcholif Diah Sri Lestari; Antonius Cahya Prihandoko; Dian Kurniati; Abi Suwito (MASI Mandiri Edukasi, 2026)
The low level of numeracy skills among junior high school students in linear function topics indicates the need for more contextual and meaningful mathematics instruction. This study explores the integration of Culturally Responsive Teaching (CRT) through the incorporation of local Banyuwangi culture as an instructional context to enhance students’ numeracy skills. Local cultural elements such as the Petik Laut tradition, Kawah Ijen tourism, Osing traditional house architecture, and Banyuwangi community economic activities were embedded in learning modules, student worksheets, and numeracy assessment tasks related to linear functions. Employing a research and development approach with a modified 4D model, this study involved eighth-grade students from a junior high school in Banyuwangi. The results indicate that the CRT-based learning materials grounded in Banyuwangi culture met the criteria of validity, practicality, and effectiveness. Furthermore, the implementation resulted in significant improvements in students’ numeracy skills, as indicated by complete learning mastery and moderate to high n-gain scores. These results suggest that positioning local culture as a source of mathematical contexts within a CRT framework not only enhances students’ understanding of linear functions but also fosters more relevant, meaningful, and culturally connected mathematics learning.